Prevalence, molecular identification and genotyping of the crayfish plague pathogen, Aphanomyces astaci in major narrow-clawed crayfish (Pontastacus leptodactylus Eschscholtz, 1823) populations from Türkiye - Akhan Süleyman; Çağatay İfakat Tülay; Berber Selçuk; Taştan Büşra; Taştan Yiğit; Dalar Tuba (Journal of Veterinary Research)
Crayfish plague is considered the most important crayfish disease globally. It is caused by the fungus-like agent, Aphanomyces astaci. This study aimed to identify and determine the prevalence of A. astaci using PCR in narrow-clawed crayfish (Pontastacus leptodactylus) populations from across Türkiye.